1-3 John : a general reader - Harrison, J. Klay.; Foster, Chad M. (Wilmore, KY : GlossaHouse, 2013)
"A tier 3 resource designed to build confidence in understanding Greek and to encourage the reading of the Greek New Testament by providing: vocabulary glosses, morphological explanations and translation helps."
1 John / J. Klay Harrison -- 2-3 John / Chad M. Foster.
Includes bibliographical references.
Text in English and Koine|| Greek.
Keywords: Bible. -- Translating; Bible. -- Translating; Bible. -- Translating; Greek language, Biblical -- Translating into English